A median loss control chart for monitoring quality loss under skewed distributions. Issue 17 (22nd November 2017) - Yang, Su-Fen; Zhou, Ruoyu; Lu, Shan-Wen
ABSTRACT: The quality and loss of products are crucial factors separating competitive companies in global market. Firms widely employ a loss function to measure the loss caused by a deviation of the quality variable from the target value. Monitoring this deviation from the process target value is important from the view of Taguchi's philosophy. In reality, there are many situations where the distribution of the quality variable may not be normal but skewed. This paper aims at developing a median loss (ML) control chart for monitoring quality loss under skewed distributions. Both the cases with fixed and variable sampling intervals are considered. Numerical results show that the ML chart with (optimal) variable sampling intervals performs better than the ML chart in detecting small to moderate shifts in the process loss centre or in the difference of mean and target and/or variance of a process variable. The ML chart and the ML chart with variable sampling intervals also illustrate the best performance in detection out-of-control process for a process quality variable with a left-skewed distribution. A numerical example illustrates the application of the proposed control chart.